1994
DOI: 10.1103/physrevb.50.16424
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic-ferromagnetic phase transition during growth of ultrathin Co/Cu(001) films

Abstract: We have investigated the magnetic response of ultrathin paramagnetic Co/Cu(001) films in an applied field using the magneto-optic Kerr effect. We find that the paramagnetic susceptibility y increases sharply upon Co deposition within a narrow thickness range close to the critical thickness at which the onset of ferromagnetism occurs. %'e attribute the observed behavior to a geometrical, or percolation phase transition, since the corresponding critical exponent y = -,', =2.39 agrees well with the experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…This has been ascribed to a suppressed Curie temperature due to either a finite size effect and/or intermixing of Co with Cu at the interfaces. 1,18,[21][22][23] Interestingly, for the thinnest multilayer films examined in this study, 0.56 ML cobalt, a superparamagnetic response was clearly observed at room temperature, although the saturation moment was substantially reduced to ϳ30% of the bulk value. One important distinction between prior studies and the results reported here is the deposition rate.…”
Section: Resultsmentioning
confidence: 77%
“…This has been ascribed to a suppressed Curie temperature due to either a finite size effect and/or intermixing of Co with Cu at the interfaces. 1,18,[21][22][23] Interestingly, for the thinnest multilayer films examined in this study, 0.56 ML cobalt, a superparamagnetic response was clearly observed at room temperature, although the saturation moment was substantially reduced to ϳ30% of the bulk value. One important distinction between prior studies and the results reported here is the deposition rate.…”
Section: Resultsmentioning
confidence: 77%
“…[1][2][3][4][5][6][7] One of the main reasons for this choice was the excellent layer-by-layer growth of this system. 8 Below 2 ML, however, controversial results were published about the growth of Co/Cu͑001͒.…”
Section: Introductionmentioning
confidence: 99%
“…The complicate structure of films below 2 ML resulted in controversial works on the magnetic properties such as the Curie temperature (T c ) and the type of magnetic ordering ͑ferromagnetism, superparamagnetism, etc.͒. For example, it was reported that 1.6 ML is the thickness for the onset of room-temperature ferromagnetism 4,7 and below 1.6 ML Co/Cu͑001͒ is in a paramagnetic state because of the absence of magnetic anisotropy. 4 Later on, a clear jump of about 100 K in the Curie temperature (T c ) at a critical coverage d c of about 1.8 ML Co/Cu͑001͒ was observed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism for long-range order was proposed for Co/Cu͑001͒. 2 For further study of the magnetic interaction in nanometer-scale structures, however, these random networks of magnetic islands are not suitable for macroscopic measurements of spatially averaged quantities because of inhomogeneities in the lateral size and the thickness of the magnetic islands. In order to study the size and shape dependence of the magnetic interaction, controlled fabrication of ordered nanometer-scale structures is required.…”
Section: Introductionmentioning
confidence: 78%